Battery assisted four-wheel weeder for reducing drudgery of farmers - SINGH, MUKESH K; SINGH, S P; SINGH, M K; EKKA, UTPAL (The Indian Journal of Agricultural Sciences, 2019)
Mechanical methods of weeding are preferred over other methods of weed control because of their added advantages of simple construction, low cost and environmental friendly. Mechatronics concept was incorporated in development of a battery-assisted four-wheel weeder for weeding operation in wide row (more than 30 cm) crops. The developed machine consisted of brushed DC motor, DMSC, battery, power transmission system, drive-wheels, front wheels, frame and swinging handle. A brushed DC motor of 250W powered by 24V-14Ah battery with sweep type weeding tool performed satisfactorily in the field for weeding operation up to 147N draft.The operators are to only guide the weeder up to 147N draft while they need to apply their muscle power beyond 147N to prevent slippage.The average field capacity with this machine was 0.0554 ha/h at walking speed of 2.52 km/h with 97.5% weeding efficiency. The machine is gender-friendly with simple in design and technology and has potential to be adopted by small and hill farmers with reduced drudgery. The concept of transforming manual operated to battery assisted weeder was found satisfactory for wide row crops.